SYNTHESIS, CHARACTERIZATION, AND IN VIVO IMMUNOMODULATION OF CCR2 AND VASCULAR ENDOTHELIAL GROWTH FACTOR ANTAGONISTS-LOADED PEGYLATED NANOPARTICLES - Abd-rabou, Ahmed A; Ahmed, Hanaa H; Kishta, Mohamed S (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Chemokine (C-C motif) ligand 2 (CCL2), a candidate of cytokines, orchestrates immune cell recruitment to inflamed organs. CCL2 has been shown to have direct angiogenic effects, so providing an anti-angiogenic agent, Avastin (AV), to be combined with the CCR2 antagonist (concentration ratio [CR]) plays an essential role in the hemostatic strategy for immunomodulation. Lack of targetability and the adverse effects of chemical treatments are the main obstacles led scientists to develop novel strategies using nano-delivery approaches such as pegylated nanoparticles (NPs) which exhibits reduced drug clearance rates. The rationale of the current study is to test the in vivo immunomodulatory effects of AV and/or CR in their NPs or free counterparts. Methods: These NPs were synthesized and characterized using different physicochemical techniques. Males Wistar rats (n=114) were used and divided into 7 groups treated with vehicle, AV, AVNP, CCR2 antagonist (CR), CCR2 antagonist NPs (CRNP), AV-CCR2 antagonist (AVCR), and AV-CCR2 antagonist NPs (AVCRNP). Groups were subdivided into three subgroups according to the administrated dose. Blood was taken from rats for differential leukocyte and platelet profile measurements. Sera were collected to test vascular endothelial growth factor (VEGF) levels. Autopsy samples from liver were taken for histopathological investigation. Results: The morphology of the NPs was spherical and had sizes ranging from 89.89 nm to 146 nm. Monocytes and lymphocytes accumulated in the blood circulation and VEGF levels were inhibited after AV and CR administrations. In addition, large platelets concentration ratio was elevated in the blood circulation. Conclusion: We concluded that AV ad CR therapeutic regimens have an immunomodulatory role through induction of monocyte-platelet aggregation and inhibition of VEGF.